2004
DOI: 10.1177/088572880402700203
|View full text |Cite
|
Sign up to set email alerts
|

Giving Voice to Students with Disabilities Who Have Successfully Transitioned to College

Abstract: A qualitative study, using the journals of 22 university students with disabilities, was conducted in order to learn more about their transitioning process and success in college. Findings include identification of the skills, abilities, and knowledge that college students with disabilities perceived as contributing to their transition to and success in college. The following major themes were identified. College students with disabilities (a) are insightful and reflective regarding their transition and postse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…These findings affirm the importance of self-advocacy (Adams & Proctor, 2010;Daly-Cano et al, 2015;Hadley, 2006;Janiga & Costenbader, 2002;Webster, 2004) and extend the literature by highlighting a direct connection between self-advocacy and the development of a sense of belonging. Student narratives also suggest that self-advocacy leads to greater mastery of the student role, which aligns with the literature showing how effective self-advocacy relates to collegiate adjustment and academic achievement; yet some scholars (Daly-Cano et al, 2015;Janiga & Costenbader, 2002) suggest many first-year students can be unprepared to effectively or proactively self-advocate.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings affirm the importance of self-advocacy (Adams & Proctor, 2010;Daly-Cano et al, 2015;Hadley, 2006;Janiga & Costenbader, 2002;Webster, 2004) and extend the literature by highlighting a direct connection between self-advocacy and the development of a sense of belonging. Student narratives also suggest that self-advocacy leads to greater mastery of the student role, which aligns with the literature showing how effective self-advocacy relates to collegiate adjustment and academic achievement; yet some scholars (Daly-Cano et al, 2015;Janiga & Costenbader, 2002) suggest many first-year students can be unprepared to effectively or proactively self-advocate.…”
Section: Discussionsupporting
confidence: 81%
“…Multiple researchers have found that selfadvocacy is critical in the transition to, and persistence through, postsecondary education (Adams & Proctor, 2010;Daly-Cano, Vaccaro & Newman, 2015;Getzel & Thoma, 2008;Hadley, 2006;Janiga & Costenbader, 2002;Thoma & Wehmeyer, 2005;Webster, 2004). Despite these benefits, some students with disabilities come to college unprepared to self-advocate because of past reliance on parents, special education teachers, and a secondary school system that did not require self-advocacy (Janiga & Costenbader, 2002).…”
Section: Self-advocacymentioning
confidence: 99%
“…Self-determination (SD), or the ability to identify and achieve one’s own set goals (Field and Hoffman 1994), has been found to predict better post-school outcomes in typically developing individuals as well as among students with other disabilities (e.g., Chambers et al 2007; Deci and Ryan 2002; Wehmeyer and Palmer 2003). Knowledge about one’s disability, as well as its associated strengths and difficulties, is critical to SD (Hitchings et al 2001; Webster 2004). To target SD, STEPS focuses on building self-knowledge (e.g., about ASD, challenges in college), self-advocacy, and goal-directed behavior.…”
Section: Development Of the Steps Programmentioning
confidence: 99%
“…Además señalar que el factor discapacidad es el único que marcó diferencias según el tipo de desarrollo vocacional, en el sentido de a mayor desarrollo vocacional eficaz menor es su influencia en la elección vocacional. Así mismo, algunos estudios realizados con titulados universitarios discapacitados (Gill 2007;Webster, 2004) afirman que este tipo de población presenta características propias como: la capacidad de perseverar en sus logros, tener alta autoestima, enfocarse en acciones posibles, no frustrarse ante fracasos, etc. Lo que confirma que la discapacidad no juega un papel de limitación, si no de motivación para su propia trayectoria personal y profesional con la intención de poner a prueba su valía y eliminar de su entorno más próximo los diferentes estereotipos o etiquetas que han ido asumiendo a lo largo de su trayectoria escolar y formativa.…”
Section: Conclusionesunclassified